Retinal Support by a Dual-Phase Microencapsulated Carotenoid–Polyphenol Matrix Featuring Lutein, β-Carotene, Blueberry Extract, and Grape Seed Extract: Formulation Performance and Evidence-Based Ocular Protection - Yassine, Jabar; Cárdenas, Ricardo; Semenza, Gregg L. (International Journal of Agriculture and Food Sciences Research, 2026)
We evaluated an NVTIA retinal-support matrix centered on lutein, β-carotene, blueberry extract, and grape seed extract, while preserving the formulation-performance dataset and matching it with published clinical and mechanistic evidence. We reviewed peer-reviewed literature in PubMed and authoritative NIH/NEI materials through March 2026, and we aligned those data with the engineering endpoints retained in the formulation dataset: lipid-phase oxidation, water-phase retention, 45-minute dissolution, and retinal pigment epithelial (RPE) cell survival under blue-light stress. In the formulation dataset, the optimized embodiments showed markedly lower oxidation (0.8–1.2% vs 15.6%), higher retention (97.5–99.2% vs 72.3%), higher 45-minute dissolution (88.3–92.5% vs 65.7%), and higher RPE survival (82.4–89.7% vs 65.2%) than the conventional control. Published evidence provided clinical support for the carotenoid axis: AREDS/AREDS2 supplementation reduces progression from intermediate to advanced age-related macular degeneration (AMD) by about 25%, and long-term follow-up showed lutein/zeaxanthin to be a safer and more effective replacement for β-carotene in populations at risk of smoking-related harm [1–3]. A randomized trial in early AMD further showed that lutein/zeaxanthin supplementation increased macular pigment optical density and improved visual function [4], while macular carotenoid supplementation improved photostress recovery and disability glare in healthy adults [5]. Human and preclinical studies also support complementary roles for anthocyanin- and proanthocyanidin-rich fractions from blueberry/bilberry and grape seed sources in visual fatigue, oxidative retinal injury, and diabetic retinal pathology [6–12]. Together, these data indicate that a dual-phase protected carotenoid–polyphenol architecture is biologically plausible and translationally relevant, with the strongest human support still favoring lutein-containing, β-carotene-restricted retinal nutrition strategies.